Infeksi Avian Paramyxovirus Tipe-1 pada Babi di Bali (AVIAN PARAMYXOVIRUS TYPE-1 INFECTION IN PIG IN BALI) - Mirah Adi, Anak Agung Ayu; Putra, I Gusti Agung Arta; Setiabudi, Bayu; Kardena, I Made; Astawa, Nyoman Mantik (Jurnal Veteriner; Vol 16 No 1 (2015), 2015)
Avian Paramyxovirus type 1 (APMV-1) is a virus infecting birds with mortality level varies accordingto its pathotype. Although the virus is normally originated from birds, the recent report showed that it canbe isolated from pig. In order to find out APMV-1 infections on pig in Bali, a serologic study was conductedto detect the antibody against APMV-1 among pigs in Bali. Indirect enzyme-linked immunosorbentassay (ELISA) was used to detect the antibody against APMV-1 in pig sera. The serum samples withoptical density value over the cut off value (COV) was considered as those containing Ab against APMV-1. Of 215 samples collected from traditional farms of eight regency and city in Bali namely Negara,Tabanan, Badung, Denpasar City, Gianyar, Bangli, Karangasem and Buleleng Regency, 174 samples(80,93%) were positive antibody against APMV-1. On the other hand, there were 125 (98,42%) positivesample among 127 sample collected from Pesanggaran abattoir. Furthermore, the 8-9 month age pigsshowed that their antibody against APMV-1 were higher (p<0.01) than those of 3-6 months age. TheELISA positive samples were further confirmed using Western immunoblotting assay. The anti-APMV-1antibody positive sera reacted with the virus specific protein band of 258 kDa and the negative sera did notreact with the viral protein. As pig has never been vaccinated with APMV-1 vaccine, the presence of Abagainst APMV-1 showed that the pigs were naturally infected with APMV-1.
Keywords: APMV-1, ELISA, Western immunoblotting